2022
DOI: 10.3389/fcell.2022.664261
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic Stem Cell Factors: Their Functional Role in Self-Renewal and Clinical Aspects

Abstract: Hematopoietic stem cells (HSCs) possess two important properties such as self-renewal and differentiation. These properties of HSCs are maintained through hematopoiesis. This process gives rise to two subpopulations, long-term and short-term HSCs, which have become a popular convention for treating various hematological disorders. The clinical application of HSCs is bone marrow transplant in patients with aplastic anemia, congenital neutropenia, sickle cell anemia, thalassemia, or replacement of damaged bone m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 241 publications
(355 reference statements)
0
19
0
Order By: Relevance
“…Importantly, this higher proliferative response in IL-1α-treated Tet2 +/-HSCs could not be clearly attributed to differences in gene expression of IL-1 pathway members (Supplemental Figure 5B). Having observed that Tet2 +/-HSPCs maintain a higher self-renewal and repopulation capacity upon IL-1α treatment compared to WT counterparts (Figure 4E), we focused the analysis on genes implicated in HSC self-renewal [30][31][32][33][34][35][36][37] . While most genes were significantly downregulated in both WT and Tet2 +/-HSCs HSCs upon chronic IL-1α exposure (22 genes.…”
Section: Tet2 +/-Hscs Exposed To Il-1α Upregulate Proliferation and M...mentioning
confidence: 99%
“…Importantly, this higher proliferative response in IL-1α-treated Tet2 +/-HSCs could not be clearly attributed to differences in gene expression of IL-1 pathway members (Supplemental Figure 5B). Having observed that Tet2 +/-HSPCs maintain a higher self-renewal and repopulation capacity upon IL-1α treatment compared to WT counterparts (Figure 4E), we focused the analysis on genes implicated in HSC self-renewal [30][31][32][33][34][35][36][37] . While most genes were significantly downregulated in both WT and Tet2 +/-HSCs HSCs upon chronic IL-1α exposure (22 genes.…”
Section: Tet2 +/-Hscs Exposed To Il-1α Upregulate Proliferation and M...mentioning
confidence: 99%
“…Functional analysis and pattern distribution (Fig. 3F) confirmed that HSCs selectively express genes regulating quiescence (P1, P12: SOCS2, TAL1, HOPX) 32,33 or self-renewal (P9-10: HLF, MLLT3, MEIS1) 34 , as well as early regulators of erythro-megakaryocytic differentiation (P11: AMPD3, MYH10).…”
Section: Cd127and Cd127 + Elps Differentiate From Bipotent Mlpsmentioning
confidence: 74%
“…The bone marrow contains a heterogeneous population of progenitor cells, among which hematopoietic and mesenchymal stem cells play a leading role [4]. The direct isolation of these cells from the bone marrow is a direct aspiration of the ilium contents followed by passages through needles of decreasing diameter in order to create a suspension of cells and separate two germ fractions according to their ability to quickly adhere acquiring a fibroblast-like structure corresponding to mesenchymal stem cells.…”
Section: Methods and Principles Of Stem Cell Isolationmentioning
confidence: 99%